Fabrication of gelatin-heparin based cartilage models: enhancing spatial complexity through refinement of stiffness properties and oxygen availability - Lindberg, G.; Norberg, A.; Soliman, B.; Jüngst, T.; Lim, K.; Hooper, G.; Groll, J.; Woodfield, T. (Frontiers in Biomaterials Science, 2024)
The intricate nature of native cartilage, characterized by zonal variations in oxygen levels and ECM composition, poses a challenge for existing hydrogel-based tissue models. Consequently, these 3D models often present simplified renditions of the native tissue, failing to fully capture its heterogenous nature. The combined effects of hydrogel components, network properties, and structural designs on cellular responses are often overlooked. In this work, we aim to establish more physiological cartilage models through biofabrication of photopolymerizable allylated-gelatin (GelAGE) and Thiolated Heparin (HepSH) constructs with tailorable matrix stiffness and customized architectures. This involves systematically studying how the native glycosaminoglycan Heparin, hydrogel stiffness, and oxygen availability within 3D structures influence chondrogenic differentiation and regional heterogeneity. A comprehensive library of 3D hydrogel constructs was successfully developed, encompassing GelAGE-HepSH hydrogels with three distinct stiffness levels: 12 kPa, 55 kPa and 121 kPa, and three unique geometries: spheres, discs, and square lattices. In soft GelAGE-HepSH hydrogels, the localization of differentiating cells was observed to be irregular, while stiff hydrogels restricted the overall secretion of ECM components. The medium-stiff hydrogels were found to be most applicable, supporting both uniform tissue formation and maintained shape fidelity. Three different 3D architectures were explored, where biofabrication of smaller GelAGE-HepSH spheres without oxygen gradients induced homogenous, hyaline cartilage tissue formation. Conversely, fabrication of larger constructs (discs and lattices) with oxygen gradients could be utilized to design heterogenous cartilage tissue models. Similarly, temporal oxygen gradients were observed to drive interconnected deposition of glycosaminoglycans (GAGs). Control samples of GelAGE without HepSH did not exhibit any notable changes in chondrogenesis as a function of stiffness, architectures, or oxygen concentrations. Overall, the incorporation of HepSH within GelAGE hydrogels was observed to serve as an amplifier for the biological effects from both stiffness and oxygen cues. In conclusion, fabrication of GelAGE-HepSH constructs designed to impose limitations on oxygen availability induce more zone-specific cartilage tissue alignment. This systematic study of matrix components, network stiffness, and oxygen levels in 3D biofabricated structures contributes to the development of more physiologically relevant cartilage models while further enhancing our overall understanding of cartilage tissue engineering.